Digital portfolio: A tool for learning physics (2021)
The digital portfolio is a student-student, student-teacher interaction tool where formative assessment plays an important role in the learning of physics, with which the progress of students is monitored, the entire training process is evaluated and supported of the student, according to the planning and contents of the physics course. Therefore, this article describes the use of the digital portfolio as a tool for learning in students of a teacher training program in natural sciences and environmental education at a public university in Colombia. It is a quantitative study with a non-experimental design. The research subjects were students taking the subject of basic physics. The results indicate that students perceive the portfolio as a tool that allows monitoring and reflection of their learning and favor the integration of what they have learned, which supports the use of this tool, in accordance with the results of evaluation of the students' formative process. However, the use of the portfolio requires a continuous process of change and innovation, monitoring and permanent feedback between the teacher and the students.